Prediction of continuous B-cell epitopes an integrative approach based on structural-energetic analysis - Caoili, Salvador Eugenio C. (National Institute of Molecular Biology and Biotechnology, College of Science, University of the Philippines Diliman, 2010)
In view of the rapidly evolving global double burden of infectious and non-infectious diseases, the expedient development of novel vaccines and immunodiagnostics is a public-health imperative. However, it remains a largely elusive goal despite long-standing efforts to design these biomedical products on the basis of nucleic acid sequences, protein structures and other available biomolecular data. This shortcoming is arguably a consequence of attempts at B-cell epitope prediction without regard for key physicochemical and biological aspects of the intended practical applications, especially vaccine design. Accordingly, the present work establishes the framework for an alternative approach to B-cell epitope prediction. This is accomplished primarily by relating antigen structure to the thermodynamics of paratope-epitope interaction via structural energetics in a manner that explicitly models immunologic imprinting, particularly in relation to immunodominance. The overall approach thus developed distinguishes between cross-reactions of antipeptide antibodies with proteins and of antiprotein antibodies with peptides, which follows from the application of structural-energetic analysis in conceptualizing B-cell epitope prediction for the development of vaccines and immunodiagnostics. More importantly, the overall approach enables rational B-cell epitope prediction on the basis of well-established physicochemical and biological principles pending resolution of problems that preclude definitive benchmarking of predictive methods, particularly with regard to peptide-based vaccine design for which sufficiently qualified benchmark data have yet to be generated.